(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate diagnostic accuracy of MDCT in diagnosis of fungal sinusitis. Study Design: Cross sectional study. Place and Duration of study: This study was conducted at the Department of Radiology PNS SHIFA Hospital Karachi from 18th April 2012 to 17th October 2012. Materials and Methods: 126 patients of all ages and gender with clinical suspicion of fungal sinusitis were included in the study. Non-contrast enhanced axial and coronal CT performed on 16slice MDCT. 76%patients were male, 24% female, 98.4% were immunocompetent and 1.6% were immunocompromised. CT finding of mucosal thickening with hyper-attenuating areas in effected sinuses was considered CT diagnostic criteria for fungal sinusitis. Biopsy and histopathology performed in every case and histopathological diagnosis was considered as ‘Gold standard’ for comparison of CT findings. Findings of every patient were recorded on a specially designed Performa. SPSS version 10 used to calculate diagnostic accuracy of MDCT in fungal sinusitis. Results: 32 (25.4%) patients showed mucosal thickening with internal hyper-attenuating areas in the sinuses representing fungal rhinosinusitis. Results compared with biopsy reports. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of CT scan in detection of fungal sinusitis were 100%, 93%, 78%, 100% and 94%. 5 (4%) patients showed intraorbital extension and 3 (2.4%) patients showed both intraorbital and intracranial extension of disease. Conclusion: MDCT is very useful and accurate in diagnosis of fungal sinusitis. It should be considered as first investigation of choice to confirm or to rule out fungal sinusitis in clinically suspected patients. MRI should supplement MDCT in those cases of fungal sinusitis in which intraorbital or intracranial extension of disease is suspected.